Diagnostic and statistical manual of mental disorders DSM-5. (American Psychiatric Association, 2013)
This new edition of the American Psychiatric Association's Diagnostic and Statistical Manual of Mental Disorders (DSM-5(R)), used by clinicians and researchers to diagnose and classify mental disorders, is an authoritative volume that improves diagnoses, treatment, and research.